What do children think about doctors' communication at the Teddy Bear Hospital?. (10th August 2021) - Moore, David Edward; White, Andrew; Jordan, Brigid; Uahwatanasakul, Wonie
Abstract : Aim: Excellent communication is essential for health professionals working with children. Teddy Bear Hospital (TBH) is an innovative method of developing paediatric communication skills in health‐care students. By exploring the child's perspective of medical students' communication at the TBH, we sought to better understand the role TBH plays in the development of the communication skills in medical students. Methods: Semi‐structured interviews were conducted with 31 children, aged 3–8 years old, who were attending a TBH run by third year medical students at the Royal Children's Hospital in Melbourne. These interviews were recorded and transcribed after which themes were generated by inductive content analysis using the programme NVivo 12 . Results: Children used mostly positive language when describing interactions with teddy doctors. However, almost half of the children could not recall the medical students explaining why their teddy was sick or how their teddy would get better. Furthermore, many teddies returned from TBH with medical issues different to their initial presentation. Conclusions: The communication described at TBH was overwhelmingly positive with children describing little difference between medical students and actual doctors. However, the mismatch in teddy medical issues before and after a visit to TBH along with the lack of understanding on teddy health management plans, suggests the need for further evidence‐based training in communication skills for medical students to improve their ability to communicate with very young children.